Expression and bioinformatics analyses show HSP70 complements BCL2 action in oral carcinogenesis - Geeta Singh; Rahul Pandey; Ekta R. Anthony; Shaleen Chandra; Divya Mehrotra (Elsevier, 2022)
Oral squamous cell carcinoma (OSCC) is a major form of oral malignant tumors (oral cancer) with less than 50% five year survival rate. Its pathogenesis involves dysregulation in apoptosis. Early dysregulation at molecular level could not be correlated with clinical presentations because of complex interactions at molecular levels. HSP70 (Heat shock Protein 70) and BCL2 (B cell lymphoma 2) are known molecular players in oncogenesis. However, their interaction is not known till date. Expression analyses of BCL2 and HSP70 was done through Enzyme Linked Immunosorbent Assay (ELISA) and Bioinformatic tools using blood samples from 41 OSCC, 35 Oral Potentially Premalignant Disorders (OPMD) and 4 controls in BCL2 study and 48 OSCC and 32 OPMD cases in HSP70 study. Bioinformatic software showed experimentally determined interaction value of 0.32 amongst the two, predicting similarity in molecular functions or pathways between the two, which was confirmed by ELISA. Our data showed that first HSP70 boosts BCL2 while in later stages of oncogenesis BCL2 consumes HSP70. Both molecules interact at several steps by complementing and supplementing each other. Because of this complex interaction various anti BCL2 therapies have not achieved desired results till date.